Cultural Hegemony Portrayed in Cutting Edge Pre-Intermediate Textbook (2020)
The use of textbooks in the EFL classroom is a trend that shapes the way language teachers teach and how students learn. Teachers design and use a great deal of materials for teaching and developing foreign language skills, but in terms of culture, they usually prefer to trust publishing houses for the cultural content included in their textbooks. What we do not know is that most of these textbooks promote hegemony and standardization of cultures under the conscious or unconscious ideology of the colonization of being. Teachers need to learn how to analyze and unveil the hidden mechanisms of colonization that are portrayed in some textbooks, a process which can be carried out through the use of Critical Discourse Analysis.